PERANAN LEMBAGA KEUANGAN MIKRO DAN KONTRIBUSI KREDIT TERHADAP PENDAPATAN KOTOR UKM RUMAHTANGGA SETELAH MENJADI KREDITUR (STUDI KASUS BMT MU@MALAT ) - Shofia Nur Awami (Universitas Wahid Hasyim, 2009)
Global crisis in 2008, there was a proud in economic development,because informal sector oppositely grow rapidly. Data from Statistic bureaumention that the increasing grew faster, became 47,7 million in 2007period. The problem was financing. BMT Mu@malat as the one of nonbanking financial institution is under hierarchy of Kota SemarangCooperation Department, it was stated under Wahid Hasyim Universityarea. The research was meant to know about contribution of creditassessment to brutto income and what’s the influence factor after this. Therespondent was Marginal Sector client. Result from this was the assessmentof BMT Mu@malat gave contribution of brutto income of 9,07 % permonth, function and the existence was needed to support of peopleeconomy.